USING THE BALANCED SCORECARD FOR THE PERFORMANCE MANAGEMENT OF STATE UNIVERSITIES IN ROMANIA - Marian ȚAICU; Claudia BURTESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Performance is a widely debated concept in the literature, especially in the field of business. The performance of a public institution in general, and of an educational institution in particular, is much more difficult to quantify, mainly because of the specifics of the activity and the form of funding. Simply measuring performance is not enough to improve it, and the need arises to implement a performance management system. The Balanced Scorecard is widely used in Romania and has been implemented over the last two decades in both public institutions and companies. This paper aims to propose a Balanced Scorecard for the performance management of state universities in Romania.